Understanding Dioxygen Activation in the Fe(III)-Promoted Oxidative Dehydrogenation of Amines: A Computational Study - Ricardo D. Páez-López; Miguel Á. Gómez-Soto; Héctor F. Cortés-Hernández; Alejandro Solano-Peralta; Miguel Castro; Peter M. H. Kroneck; Martha E. Sosa-Torres (Inorganics)
Hydrogenation and dehydrogenation reactions are fundamental in chemistry and essential for all living organisms. We employ density functional theory (DFT) to understand the reaction mechanism of the oxidative dehydrogenation (ODH) of the pyridyl-amine complex [FeIIIL3]3+ (L3, 1,9-bis(2′-pyridyl)-5-[(ethoxy-2″-pyridyl)methyl]-2,5,8-triazanonane) to the mono-imine complex [FeIIL4]2+ (L4, 1,9-bis(2′-pyridyl)-5-[(ethoxy-2″-pyridyl)methyl]-2,5,8-triazanon-1-ene) in the presence of dioxygen. The nitrogen radical [FeIIL3N8•]2+, formed by deprotonation of [FeIIIL3]3+, plays a crucial role in the reaction mechanism derived from kinetic studies. O2 acts as an oxidant and is converted to H2O. Experiments with the deuterated ligand L3 reveal a primary C-H kinetic isotope effect, kCH/kCD = 2.30, suggesting C-H bond cleavage as the rate-determining step. The DFT calculations show that (i) 3O2 abstracts a hydrogen atom from the α-pyridine aliphatic C-H moiety, introducing a double bond regio-selectively at the C7N8 position, via the hydrogen atom transfer (HAT) mechanism, (ii) O2 does not coordinate to the iron center to generate a high-valent Fe oxo species observed in enzymes and biomimetic complexes, and (iii) the experimental activation parameters (ΔH≠ = 20.38 kcal mol−1, ΔS≠ = −0.018 kcal mol−1 K−1) fall within in the range of values reported for HAT reactions and align well with the computational results for the activated complex [FeIIL3N8•]2+···3O2.